2008
DOI: 10.1097/ijg.0b013e31815c5f3f
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Pressure Response to Medication in a Clinical Setting: The Marshfield Clinic Personalized Medicine Research Project

Abstract: In this clinic-based setting, we found that treatment of glaucoma has changed over the past 20 years, with ophthalmologists more likely to begin treatment at lower baseline levels of IOP, and prostaglandin analogs the most commonly prescribed and agent to lower IOP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Reduction of IOP may prevent or delay visual field loss in patients with glaucoma or ocular hypertension;4,6 thus, monotherapy with IOP-lowering medications is standard-of-care treatment. However, many patients require multiple IOP-lowering therapies to reach their target IOP 15,91. Drug washout during concomitant administration of multiple medications44 and low adherence and persistence with complex glaucoma therapeutic regimens22,24,27 may reduce the effectiveness of multidrug regimens.…”
Section: Resultsmentioning
confidence: 99%
“…Reduction of IOP may prevent or delay visual field loss in patients with glaucoma or ocular hypertension;4,6 thus, monotherapy with IOP-lowering medications is standard-of-care treatment. However, many patients require multiple IOP-lowering therapies to reach their target IOP 15,91. Drug washout during concomitant administration of multiple medications44 and low adherence and persistence with complex glaucoma therapeutic regimens22,24,27 may reduce the effectiveness of multidrug regimens.…”
Section: Resultsmentioning
confidence: 99%
“…However, as patients with glaucoma have relatively mild subjective symptoms until their condition worsens and the efficacy of ophthalmic solutions is not easily noticeable, both the adherence to and continuity of treatment are reportedly poor [1,2]. The number of glaucoma patients who use two or more anti-glaucoma ophthalmic solutions concurrently is increasing in both Japan [3] and other countries [4]. It has been reported that the use of fewer ophthalmic solutions would decrease the burden on patients and improve adherence to treatment while at the same time reducing adverse effects [5,6].…”
Section: Introductionmentioning
confidence: 97%
“…Most patients use antiglaucoma ophthalmic solutions and it is estimated that each patient uses an average of two antiglaucoma ophthalmic solutions. 1 However, studies have revealed that glaucoma patients show poor adherence to antiglaucoma ophthalmic solutions 2 and adherence worsens with an increase in the number of antiglaucoma ophthalmic solutions used. 3 Okeke et al reported that ophthalmologists could not monitor adherence accurately.…”
mentioning
confidence: 99%